UREAPLAZMA UREALYTICUM VE CHLAMYDIA TRACHOMATIS ENFEKSİYONLARININ SEMEN PARAMETRELERİNE ETKİSİ - İrez, Tülay and ALICI, Bülent and ÖZKARA, Hamdi and AKKUŞ, Emre and YENCİLEK, Faruk and ÖCAL, Pelin and ÖZALP, Ali Uğur and HATTAT, Halim (Cerrahpaşa Medical Journal, 2014)
Background and Design.- Aim of this study is to determine the effect of urogenital Ureaplasma urealyticum and Chlamydia trachomatis infections to the semen parameters. 47 randomly chosen infertile and 22 fertile men were enrolled in this study. Semen were analysed according to WHO 1992 and morphology according to Kruger's strict criteria. Each semen specimen was tested for sperm autoantibobies, semen culture were done and specimens were tested for chlamydia trachomatis and ureaplasma urealyticum. The women in infertile couples were investigated by hormon profiles, histerosalphingographies and basal body temperatures. Results.- C. trachomatis and/ or U. urealyticum were positive in 57.5% of infertile patients while these were positive in 27% of fertile patients. There was no significant difference in sperm count and morphology while the decrease of sperm motility was significant. (p=0.0076 and 0.0114 respectively). The antisperm antibody count was positive in 36.4% of patients with positive Chlamydia and Ureaplasma infection and it was positive in 14% of patients with negative Chlamydia and Ureaplasma infection. Conclusion.- C. trachomatis and U. urealyticum are two microorganisms which may have a role in infertility.